2006
DOI: 10.1508/cytologia.71.161
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Karyotype of Five Species in Genus Macaca (Primate, Cercopithecidae) in Thailand by Using Conventional Staining, G-banding and High-Resolution Technique

Abstract: 274, 273, 273, 275, 273 and 351, 350, 350, 352, 350 respectively. Their autosome and X chromosome are similar but their Y chromosome is different. The NOR is on the short arm of chromosome 13. The largest is the metacentric chromosome. The smallest is theY chromosome. Thus X and Y chromosomes can use for identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…In a comparative study with slow loris and monkeys in Thailand, we found that slow loris, Assam macaque, M. assamensis (2n=42); long-tailed macaque, M. fascicularis (2n=42); rhesus monkey, M. mulatta (2n=42) and pig-tailed macaque, M. nemestrina (2n=42) had NORs on short arms near the centromere of autosomes pair 13 as type of metacentric chromosomes (Tanomtong et al 2006). In comparison with finding for langurs in Thailand, the result we gained demonstrated that the silvered langur, Trachypithecus cristatus (2n=44) had NORs on autosome 15 which is the satellite chromosome (metacentric chromosomes) (Bigoni et al 1997).…”
Section: Resultsmentioning
confidence: 96%
“…In a comparative study with slow loris and monkeys in Thailand, we found that slow loris, Assam macaque, M. assamensis (2n=42); long-tailed macaque, M. fascicularis (2n=42); rhesus monkey, M. mulatta (2n=42) and pig-tailed macaque, M. nemestrina (2n=42) had NORs on short arms near the centromere of autosomes pair 13 as type of metacentric chromosomes (Tanomtong et al 2006). In comparison with finding for langurs in Thailand, the result we gained demonstrated that the silvered langur, Trachypithecus cristatus (2n=44) had NORs on autosome 15 which is the satellite chromosome (metacentric chromosomes) (Bigoni et al 1997).…”
Section: Resultsmentioning
confidence: 96%